CRISPR/Cas9-AAV Mediated Knock-in at NRL Locus in Human Embryonic Stem Cells - Xianglian Ge; Haitao Xi; Fayu Yang; Xiao Zhi; Yanghua Fu; Ding Chen; Ren-He Xu; Ge Lin; Jia Qu; Junzhao Zhao; Feng Gu (Elsevier, 2016)
Clustered interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9)-mediated genome engineering technologies are sparking a new revolution in biological research. This technology efficiently induces DNA double strand breaks at the targeted genomic sequence and results in indel mutations by the error-prone process of nonhomologous end joining DNA repair or homologous recombination with a DNA repair template. The efficiency of genome editing with CRISPR/Cas9 alone in human embryonic stem cells is still low. Gene targeting with adeno-associated virus (AAV) vectors has been demonstrated in multiple human cell types with maximal targeting frequencies without engineered nucleases. However, whether CRISPR/Cas9-mediated double strand breaks and AAV based donor DNA mediated homologous recombination approaches could be combined to create a novel CRISPR/Cas9-AAV genetic tool for highly specific gene editing is not clear. Here we demonstrate that using CRISPR/Cas9-AAV, we could successfully knock-in a DsRed reporter gene at the basic motifleucine zipper transcription factor (NRL) locus in human embryonic stem cells. For the first time, this study provides the proof of principle that these two technologies can be used together. CRISPR/Cas9-AAV, a new genome editing tool, offers a platform for the manipulation of human genome.